Genotypic variations in phenology, productivity and heat-use efficiency of rainfed maize (Zea mays) in acid soils of north eastern Himalayan region - M A ANSARI; B U CHOUDHURY; N PRAKASH; S L JAT; B KUMAR; DUSHYANT MISHRA; M H ANSARI (The Indian Journal of Agricultural Sciences, 2016)
Northeastern Himalayan Region (NEHR) of India having frail landscape with unique climate, high rainfall with orography led wide spatio-temporal variation, often occurrence of droughts, terminal heat and high cloud covers causes antagonistic relationship with solar radiation. Growing of low yielding traditional genotypes susceptible to abiotic stresses including low radiation-use efficiency further decreased the productivity (<1.5 t/ha) of rainfed maize (Zea mays L.) in this region. The region needs improved genotypes to overcome these shortfalls. In present study, a field experiment was conducted during 2012 and 2013 to evaluate the performance of 15 improved genotypes and compared with popular traditional genotypes for physiological indices, radiation-use efficiency and finally, correlated with productivity. Results revealed that amongst the improved genotypes, hybrids Vivek QPM 9 followed by Prakash recorded significantly (P<0.05) higher physiological attributes and grain yield (4 860-5 055 kg/ha), which was two folds higher than the local genotype Chakhaochujak (hill) (2 081-2 113 kg/ha). Similarly, few other hybrids (HQPM 7, BIO 9681, PMH 1, PMH 4 and HM 4) also recorded significantly (P<0.05) higher (48 to 126%) grain yield over local genotypes. Estimated radiation-use efficiency indices (pheno- and helio-thermal, heat use efficiency) were significantly (P<0.05) higher in hybrids compared to local genotypes. Exploring improved genotypes suitable to rainfed hilly ecosystem, thus, promises improvement of maize productivity vis-Ã -vis food and livelihood security in the NEHR of India and other similar agro-ecological regions.